Вплив Co, V та Mo на структуру та фазовий склад ливарного сплаву АК12М2, модифікованого хромом - Ворон, М. М. (Physico-technological Institute of Metals and Alloys, 2023)
Al-Si and Al-Si-Cu aluminum alloys are widely used materials in many industries. Such alloys have a very high ability to be recycled many times repeatedly. In this case, with each cycle of reuse, they increase the amount of harmful impurities. First of all, this problem concerns the increase in iron content. Decreasing its harmful effects by adding manganese is a classic and quite satisfactory way to ensure the quality and the required level of mechanical properties of cast parts. The use of other modifiers, especially in combination with manganese and with each other, can significantly expand the possibilities of reducing the harmful effects of iron and improving the mechanical properties of such alloys. The complex effect of Co, V and Mo on the structure and phase composition of the well-known widely used AlSi12Cu2 alloy, which already contained a small amount of chromium to enhance the modifying effect of manganese, was investigated. All modifying additives were added in an amount of 0.1–0.2 wt.%. In this case, their total content did not exceed 0.3 wt.%. It is shown that the simultaneous presence of chromium with vanadium or molybdenum in the alloy leads to the formation of coarse modified phase Al15(Fe, Mn)3Si2, the size of which is about 80–150 μm. The formation of such adverse inclusions leads to the presence of chromium, which follows from a comparison with previous studies, where chromium in the alloys was absent. When cobalt is added, iron-containing phases are formed in more favorable morphology and small sizes of about 5–20 μm. Also, these phases occur in the form of closely spaced placers of small particles smaller than 10 μm.